Satisfaction in ocular prosthesis wearers: a comparison between stock eyes and custom eyes at the artificial eye centre, Krugersdorp - Gnanapragasam, U. D. (My University, 2020)
Purpose: The study is about understanding the level of satisfaction, quality of life and complications experienced by people wearing either custom or stock eyes. It is also aimed at determining which variables were correlated to their level of satisfaction and if visible amputation of an eye is associated with a wide range of psychosocial stressors. It was motivated by the fact that the problems encountered by ocular prosthesis wearers with eye conditions are under-reported in Africa. Thus, the study also sought to establish the extent and type of psychosocial stressors and complications experienced by these two types of prosthesis wearers. Setting: Artificial Eye Centre, Krugersdorp, Johannesburg, South Africa. Methods: The study was a cross-sectional, descriptive study, using a questionnaire to gather information on patients who had destructive eye surgeries, including evisceration and enucleation, and who were wearing artificial eyes. Results: There were 104 participants in this study with majority (57.3%) of them being men. About two thirds of the respondents (66.3%) were less than 40 years of age. The participants who were wearing custom eyes were 53 in total (55%) and those who had stock eyes were 51 in total (53%). Custom eye wearers were older than the stock eye wearers. Mean scores for psychological adjustment were within the normal range for both custom and stock eye-wearers. More of the custom eye-wearers felt their facial appearance had greatly improved compared to the stock eye wearers (99% versus 78%). Likewise, the custom eye-wearers had a higher percentage (53%) of face appearance satisfaction in contrast to the stock eye wearers (14%). Ocular discharge was a frequent complication experienced by both custom and stock eye wearers. There was a statistically significant difference (P<0.05) in the colour and viscosity of discharge between two types of prosthesis. There was a statistically significant association iv (P<0.05) between the type of ocular prosthesis worn and Quality of Life. Significant findings from the Quality of Life questionnaire were that slightly more than two thirds (66%) of the custom eye wearers were not affected by night driving compared to 35% of the stock eye wearers. Furthermore, evidence from this study indicated that the custom eye-wearers were more comfortable compared to the Stock eye-wearers. Conclusion: Custom eyes are associated with a better Quality of Life than stock eyes and should, wherever possible, be made available to the anophthalmic patients. However, levels of depression and anxiety in this group were low irrespective of prosthesis type, suggesting that in a resource constrained setting, the provision of stock eyes is an acceptable compromise
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine in in Ophthalmology to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2020